Interpreting the preliminary outcomes of the arrowsmith Programme: a neuroimaging and behavioural study. (3rd July 2019) - Weber, Rachel C.; Denyer, Ronan; Motamed Yeganeh, Negin; Maja, Rachel; Murphy, Meagan; Martin, Stephanie; Chiu, Larissa; Nguy, Veronique; White, Katherine; Boyd, Lara
ABSTRACT: Learning disabilities are currently conceptualised as involving underlying weaknesses in cognitive processing, which has prompted growing interest in cognitive interventions that may alleviate learning challenges. One such programme , the Arrowsmith programme, targets a broad array of cognitive domains, but has not been evaluated. This study evaluated the cognitive and academic growth of students who participated in one academic year of the Arrowsmith programme  and examined whether baseline MRI-derived myelin water fraction (MWF) and cognitive abilities were correlated with intervention outcomes. Participants demonstrated overall cognitive and academic growth as well as individual areas in which they improved after one year. Some areas of cognitive and academic growth were significantly correlated, suggesting a relationship in skill improvement. Baseline MWF and cognitive processing were related to higher or lower degrees of skill improvement in some areas. These results suggest that the Arrowsmith programme may be associated with improvements in cognitive and academic skills. In addition, they reflect the importance of considering individual characteristics at baseline when evaluating intervention outcomes.